EVALUASI KARAKTER MORFOLOGIS DAN PRODUKSI MUTAN PADI DENGAN APLIKASI PUPUK N DAN P YANG BERBEDA - Indra Maulana` Indra Maulana; Eva Sartini Bayu; Lolliei Agustina P. Putri (Universitas Sumatera Utara, 2013)
Evaluation Of Morphological Characters and Production of Mutan Rice by Aplicating N And PDifferent Fertilizer. Rice crop is the staple food for more than 1750 million people who inhabit thecountries of Asia and is a strategic political commodity, so that rice production in the country bemeasured by the availability of food for Indonesia. Through the technique of irradiation to producemutants or mutated plants with properties expected after a series of testing, selection andcertification. This reaserch using Randomized Block Design with 2 factors, nitrogen (250, 300, 350kg/ha) and phosphate (200, 250, 300 kg/ha). From the data analysis obtained that Nitrogen andPhosfat fertilized treatment perform the significant effect to the plant height, number of tillers, themaximum number of tillers, number of productive tillers panicle number, the number of paniclebranches, number of grains per panicle, 1000 grain weight, production per plant and production perhectare. treatment did not significantly affect the parameter of seed germination,time germination,he number of empty grains per panicle, the percentage of empty grains per panicle, length ofvegetative stage, length stadia generative, age of flowering , age of harvest and stem diameter.Keywords : nitrogen, phosphate, mutan, rice